Urine bacterial culture growth and association with urine sedimentation and clinical findings in cats with acute kidney injury. Issue 10 (October 2022) - Siu, Kenneth; Diaz, Amanda; Chadwick, Abigail; Keys, Deborah; Shropshire, Sarah; Summers, Stacie C
Objectives: A urine culture is often pursued in cats with acute kidney injury (AKI) to screen for bacterial growth in the urine, but it can be cost prohibitive. The aim of the study was to determine the ability of a urinalysis and lower urinary tract signs (LUTS) to predict urine culture results in cats with AKI. Methods: Ninety-seven cats with AKI were included in this study. This was a retrospective, observational study. Medical records from 2008 to 2018 were reviewed to identify cats with AKI that had a paired urinalysis and urine bacterial culture. The sensitivity, specificity, positive predictive value and negative predictive values of microscopic bacteriuria, pyuria, hematuria and the presence of LUTS for predicting urine culture results was calculated. Results: Thirty-two percent of cats (n = 31) had a positive urine culture. Of these, 28 (90%) had bacteriuria, 21 (68%) had pyuria, 13 (42%) had hematuria and 10 (32%) had LUTS. Of the 42 cats without hematuria or pyuria, seven had a positive urine culture (17%). Bacteriuria had a high sensitivity (90%) and specificity (92%) for predicting urine culture bacterial growth. The absence of bacteriuria had a high negative predictive value for no bacterial growth (95%). The odds of a positive urine culture were increased with bacteriuria (odds ratio [OR] 114, 95% confidence interval [CI] 29–621; P <0.001), pyuria (OR 21, 95% CI 7–70; P <0.001) and LUTS (OR 5, 95% CI 1.7–16; P  = 0.004). Hematuria was not associated with a positive culture (sensitivity 42%, specificity 52%). Conclusions and relevance: Microscopic bacteriuria and pyuria on urine sediment evaluation and LUTS can be helpful for predicting bacterial culture results in cats with AKI and in settings where submitting a urine culture may not be financially feasible.